1995
DOI: 10.1200/jco.1995.13.9.2174
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and clinical evaluation of a pharmacologically guided regimen of suramin in patients with hormone-refractory prostate cancer.

Abstract: We have characterized all toxicities with suramin in a pharmacologically guided phase I study designed to maintain plasma suramin concentrations of 100 to 300 micrograms/mL (cohorts 1 to 3). The incidence of grade 3 to 4 neurologic abnormalities was relatively low, particularly in cohorts 2 and 3 (100 to 250 micrograms/mL). Evidence of significant and durable antitumor activity was seen in all three cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Although the crucial role for purinergic signaling in rodent taste systems is well established, clinical evidence for its role in human gustation is scanty. A clinical study testing the effects of the broad-spectrum P2X receptor antagonist suramin reports taste disturbances in more than two-thirds of the patients tested (37). These data implicate a role for receptors containing the P2X subunit in human taste, but whether disrupted NTPDase2 function in a patient population would lead to similar taste disturbances remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Although the crucial role for purinergic signaling in rodent taste systems is well established, clinical evidence for its role in human gustation is scanty. A clinical study testing the effects of the broad-spectrum P2X receptor antagonist suramin reports taste disturbances in more than two-thirds of the patients tested (37). These data implicate a role for receptors containing the P2X subunit in human taste, but whether disrupted NTPDase2 function in a patient population would lead to similar taste disturbances remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Factors intrinsic to the bone marrow such as transferrin also reportedly may interfere with the antiproliferative effect of suramin [17]. Interestingly, a clinical report on phase I and II trials of suramin showed rather good responses of measurable prostatic cancer metastatic sites such as liver, lung, lymph nodes, and skin, but no radiographically and only minimal scintigraphically evident responses by bone metastases [2, 3]. …”
Section: Discussionmentioning
confidence: 99%
“…We have established a model of micrometastases to bone and liver in chick embryos using the hormone-independent cancer cell line PC-3 which consistently produces metastases in bone and liver. We used the model to evaluate suramin, a promising agent against hormone-refractory prostate cancer [2, 3, 4], by means of a quantitative PCR assay for micrometastases [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have confirmed the direct antitumor activity of suramin against prostate cancer, breast cancer, sarcoma and colorectal cancer cell lines [10, 11, 12, 13]. Clinical trials of suramin have reported tumor responses in patients with prostate cancer [14, 15, 16, 17, 18, 19, 20, 21, 22, 23], Kaposi’s sarcoma, non-Hodgkin’s lymphoma, renal cell carcinoma and adrenal carcinoma [9, 23]. …”
Section: Introductionmentioning
confidence: 99%